Journey of Language Instruction: An Autoethnographic Study on Teaching English to Young Learners in Indonesian Home-Schooling Environments - Aly, Abdul Hamid; Erfan Efendi (Jurnal Pendidikan Anak, 2024)
This autoethnographic study explores the dynamics of teaching English to two homeschool students, aged 6 and 13, within their home environment, focusing on personalized instructional strategies. The researcher, serving as both teacher and observer, examines the interplay of the students' unique learning styles, preferred teaching resources, and attention spans. Student A, a kinesthetic learner, benefits from interactive games and physical activities, while Student B, a visual learner, excels with structured lessons and visual aids. The use of diverse online resources, such as British Council and Duolingo, enhances engagement through gamification and multimedia elements. The study highlights the necessity of adaptable teaching methods to address varying attention spans, with Student A requiring frequent activity changes and Student B benefiting from periodic breaks during in-depth exploration. The findings underscore the effectiveness of tailored educational approaches in fostering student engagement and learning outcomes. By documenting and reflecting on these experiences, the study contributes to the broader field of educational research, advocating for the integration of personalized and technologically enriched teaching strategies in homeschooling settings. This research affirms the transformative potential of individualized instruction in nurturing academic growth and a lifelong love for learning. Keywords: Autoethnography, homeschooling, English for Young Learners, personalized instruction, educational technology.